Simplified method for calculation of the Joule–Thomson coefficient at natural gas flowrate measurement - Pistun, Yevhen; Matiko, Fedir; Masnyak, Oleh (Publishing House of Lviv Polytechnic National University, 2015)
This work deals with measurement of natural gas flowrate and volume by means of pressure differential devices. The existing methods for calculation of Joule-Thomson coefficient to be applied in pressure differential flowmeters are analyzed in the paper. A new method which uses a simplified set of parameters of gas composition, namely the density at standard conditions, the molar content of nitrogen and carbon dioxide, is developed by the authors. This method provides the possibility to calculate the Joule-Thomson coefficient within the pressure range from 0.1 MPa to 15.0 MPa and the temperature range from 250 K to 350 K. It was defined that for natural gas with density at standard conditions up to 0.75 kg/m3 and contents of nitrogen and carbon dioxide up to 5 % of each component, the relative error of the values derived according to the new developed method do not exceed 3.0 % in the specified ranges of temperature and pressure. The application of this method in calculators of flowrate and volume of natural gas will help to reduce the systematic error of flowrate and volume measurement caused by the distinction of gas temperature in the place of measurement downstream of primary device from gas temperature upstream of primary device. Подано аналіз існуючих методів розрахунку коефіцієнта Джоуля–Томсона, за результатами якого встановлено необхідність розроблення методу розрахунку на основі спрощеного набору параметрів складу газу. Представлено новий метод для розрахунку коефіцієнта Джоуля–Томсона у діапазоні абсолютного тиску газу від 0,1 МПа до 15 МПа та температури від 250 К до 350 К. Основне рівняння методу побудоване на основі принципу відповідних станів і описує залежність коефіцієнта Джоуля–Томсона від приведених температури та густини. Для обчислення приведеної густини газу запропоновано застосовувати розроблене авторами рівняння псевдокритичної густини природного газу. Виконано детальне тестування розробленого методу та встановлено, що для природних газів із густиною за стандартних умов rС£0,75 кг/м3 та вмістом азоту і вуглекислого газу до 5 % кожного, відносне відхилення значень методу від розрахункових значень коефіцієнта Джоуля–Томсона, отриманих за методом ISO 20765-1, не перевищує ±3,0% для вказаних діапазонів тиску та температури газу. Наведено приклади розрахунку систематичної похибки вимірювання витрати за допомогою витратоміра змінного перепаду тиску, зумовленої ефектом Джоуля–Томсона.
Спрощений метод розрахунку коефіцієнта Джоуля–Томсона під час вимірювання витрати природного газу
Keywords: Joule-Thomson coefficient; natural gas; methods for calculation; pressure differential flowmeters; systematic error; коефіцієнт Джоуля–Томсона; природний газ; метод розрахунку; витратомір змінного перепаду тиску; систематична похибка